Problem structuring for decision consensus among students / Dianne Lee Mei Cheong, Louis Sanzogni and Luke Houghton - Cheong, Dianne Lee Mei; Louis, Sanzogni; Houghton, Luke (Penerbit UiTM (UiTM Press), 2017)
Decision-problem structuring is conceptualized to be a process comprising activities characterized by the students. The activities are cognitive efforts of a group coming to an understanding and determining the representation of the decision-problem and of what knowledge is relevant to the decision-problem. Cognitive effort refers to the fraction of limited attention with respect to resources that are momentarily allocated to a process. The consensual representation of the decision-problem provides the basis for modeling those activities in some form and order. Knowing how a decision-problem is structured by students based on Management Information System domain will enable the modeling to be based on a simple descriptive behaviour in problem structuring. One such method would be a mathematical model to quantify the problem which ultimately becomes well-structured.